2012
DOI: 10.1002/app.36755
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a novel once‐daily formulation of diltiazem using arabinogalactan as a channeling agent

Abstract: The aim of the present study was to develop a once-daily, delayed controlled release formulation for diltiazem. Developed formulation consists of two coated tablets inserted into a capsule; the first tablet is intended to produce a fast release profile, while the second tablet with a unique controlling membrane containing arabinogalactan as a channeling agent was designed to achieve a delayed controlled release profile for diltiazem. The in vitro characteristic of formulation was determined in terms of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Once it is enzymatically broken down, the porosity generated by arabinogalactan is ideal for controlled drug release. Due to its high water solubility, biocompatibility, and biodegradability, arabinogalactan shows potential as a drug carrier [ 109 ].…”
Section: Overview On Polysaccharide-based Drug Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once it is enzymatically broken down, the porosity generated by arabinogalactan is ideal for controlled drug release. Due to its high water solubility, biocompatibility, and biodegradability, arabinogalactan shows potential as a drug carrier [ 109 ].…”
Section: Overview On Polysaccharide-based Drug Delivery Systemsmentioning
confidence: 99%
“…The formulation produced a desired delayed controlled release dissolution profile for over 24 h in buffer (pH 6.8). The surface morphology of the coating film showed channeling formation upon contact with the media [ 109 ].…”
Section: Overview On Polysaccharide-based Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the rapidly growing interest in the research of Chi, its chemical modification was done because, in its native form, its solubility in most of aqueous or other biocompatible media is negligible because of embedded functional groups. The functionalization of Chi with S atom containing molecules (thiolation) and the immersion of sulfate groups (sulfation) were chosen in several chemical modifications, such as quaternization, sulfation, thiolation, alkylation, acylation, oligomerization, carboxyalkylation, hydroxyalkylation, phosphorylation, graft copolymerization, and enzymatic and other reactions because of specific applications in anticholesterol, 12,13 anticoagulant, [14][15][16] antitumor, 17 cardiovascular disease 4,18,19 and drug delivery. [2][3][4] These studies have been reported in a most scattered and piecemeal manner, and nothing can be generalized about a common principle with respect to the methodology of functionalization and the strength of the covalent bonds formed on functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…4 and the alginate-chitosan hydrogels shown in Ref. 5) or tissue engineering (as in the dextran hydrogel scaffolds shown in Ref.…”
mentioning
confidence: 99%